Khidmat Mahasiswi KKN STIBA Makassar Melalui Pembinaan Qur’ani pada Masyarakat Kelurahan Pettuadae, Kecamatan Turikale, Kabupaten Maros - Sa'adal Jannah; Munira Munira (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
The purpose of the Real Work Lecture (KKN) of STIBA Makassar Batch IV is to realize community service which is a pillar of “Tri Dharma Perguruan Tinggi”. The method of implementing this activity is to map the problems and needs first using soar analysis instruments. After analyzing problems and needs, a work program is prepared that is appropriate and needed by the community. Successful work programs are Tahfiz Weekend For Children, Social Services, Funeral Training, and Santri Children's Festival. The result of this activity is to see the enthusiasm of the community, adults and children in every activity. They feel great benefits after participating in various KKN work programs, among which are children able to recite daily prayers and memorize some surahs in the Qur'an, Muslim women also increasingly understand the basics of Islamic science and are determined to keep learning even though this KKN program has ended. In addition, underprivileged communities also feel the benefits by lightening their burdens through social service activities.